A Touch of Culture in Learning: Teaching Materials My Food is Healthy and Nutritious for Elementary School (Journal of Basic Education Research, 2022)
Purpose of the study: This research aims to design teaching materials grounded in local wisdom and to evaluate the feasibility of these materials for the elementary/MI level, specifically focusing on Theme 9 "My Food is Healthy and Nutritious" and Subtheme 1 "My Food is Healthy and Nutritious." Methodology: The research employed the Research and Development (R&D) method utilizing the ADDIE model. The participants included one class teacher and two lecturers who provided feedback through validation questionnaires and teacher response questionnaires. Main Findings: The findings indicate that the responses from both lecturers regarding the development of teaching materials based on local wisdom were valid, with lecturer II's responses being highly valid. The teacher's feedback also confirmed the high validity of the teaching materials developed. Based on these results, it can be concluded that the designed teaching materials are suitable and effective for use in learning activities. Novelty/Originality of this study: This research represents a significant advancement in the design of teaching materials by creatively integrating local wisdom to enhance the understanding of Class IV SD/MI students about health and nutrition through Theme 9 and Subtheme 1. Adopting an innovative design approach, this study pioneers a new direction in Class IV SD/MI learning, exploring effective strategies to incorporate local wisdom into teaching materials to strengthen students' comprehension of healthy and nutritious food.